Education on the Use of People's Business Credit (KUR) Funds for MSME Development Through Radio Broadcasting - Nuning Indah Pratiwi; Kadek Amelia Devianti; Wahyu Indra Satria (LPPM UIKA Bogor, 2023)
This activity program is a non-profit program that provides socialization and community support to obtain Business Credit Funds (KUR) in Panjer Traditional Village, South Denpasar District, Denpasar City. This socialization activity aims to: 1) MSME implementers can understand the existence of monetary institutions that can provide business installments to the community. 2) MSME members who have working capital problems can request a People's Business Credit (KUR). 3) Entrepreneurial executives have the knowledge and understanding to ask for and receive people's business credit (KUR) fees to develop their businesses. This service event was founded by 30 SMEs in Panjer Traditional Village, South Denpasar District, Denpasar City. This method is made possible by socializing the provision of corporate credit to the public with simple terms and low-interest rates. As a result of this activity, people who have applied for KUR Funds can expand their knowledge and ability to receive funds for business development from their MSME members in Panjer Traditional Village, South Denpasar District, Denpasar City.